Revisão taxonômica do gênero neotropical X.eropigo Pickard-Cambridge (Araneae, Corinnidae, Corinninae) - SOUZA, Danni Roberto Santos de (Universidade Federal do Pará, 2013)
The genus Xeropigo O. Pickard-Cambridge, 1882 is revised, with the proposition of seven neotropical new species. X. candango, based in males and females from Brasília, Distrito Federal and Goiás, Brazil; X. rheimsae, based in males from Goiás, Brazil; X. camilae, in males and females from north and middle west of Brazil; X. cotijuba, in males and females from floral and middle west of Brazil; X. pachitea, based in males and females from Huánuco and Cajamarca, Peru; X. perene, in females from Junin and Loreto, Peru; X. brescoviti, in males from Bení, Bolivia. The previously known species, X. tridentiger (O. Pickard-Cambridge, 1869), type-species, described from Santa Helena Island, Atlantic Ocean, but also known from South and Central Americas, and X. smedigaari (Caporiacco, 1955) from North Venezuela and Trinidad, are readgnosed. New records and illustrations of X. tridentiger are given.